Composite material and preparation method thereof, and current collector
By blending the solid electrolyte into the covalent grafted polyolefin to form a composite material, the problems of poor safety and high brittleness of solid electrolytes are solved in traditional lithium-ion batteries, and the performance and safety improvement of electrolyte are achieved.
Patent Information
- Application Number
- CN202411418729.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-12
AI Technical Summary
Traditional lithium-ion batteries are prone to safety problems such as fire or explosion due to heavy impact or puncture during use, and the existing NASICON and garnet solid electrolytes have problems such as high brittleness and poor batch processing performance.
By blending solid electrolytes into covalently grafted polyolefins, a composite material is formed, disrupting the order of the polymer molecular chain, increasing porosity and flexibility, inhibiting the production of lithium dendrites, and improving the electrochemistry of the electrolytes Performance and mechanical properties.
It effectively improves the electrochemical performance, mechanical properties and ionic conductivity of the electrolyte, reduces the safety risks of lithium batteries during circulation, and improves the safety and performance of the batteries.
Smart Images

Figure CN118919827B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite material containing a solid electrolyte and a covalently grafted polyolefin, a preparation method thereof, and a current collector. Background Art
[0002] With the rapid development of science and technology, rechargeable ion batteries with long cycle life and high specific energy have become the future trend. Lithium-ion secondary batteries are rapidly being used in electric vehicles, power storage systems and smart grids, increasing the demand for rechargeable lithium batteries with larger capacity, higher energy density, better safety and longer cycle life. Traditional lithium-ion batteries are prone to fire or explosion and other safety issues when they encounter external force or puncture during use.
[0003] As high-performance solid electrolytes, NASICON and garnet solid electrolytes have the characteristics of good thermal stability, wide stable potential window, and high ionic conductivity at room temperature, but they are also brittle and have poor batch processing performance, making them difficult to be directly applied to lithium battery structures. In addition, the electrochemical stability window of ordinary gel polymers is low, making it difficult to match high-potential positive electrode materials, thus limiting their application in high-voltage lithium batteries. Summary of the invention
[0004] The present invention provides a composite material containing a solid electrolyte and a covalently grafted polyolefin, which increases the porosity, reduces the crystallinity, and increases the flexibility of the polymer chain by disrupting the order of the single polymer molecular chain to a certain extent through the covalently grafted polyolefin, thereby effectively inhibiting the generation of lithium dendrites during the cycle. In addition, the solid electrolyte is mixed into the covalently grafted polyolefin to improve the electrochemical properties and mechanical properties of the electrolyte and improve the ionic conductivity.
[0005] The first scheme of the present invention is implemented as follows: a composite material includes: a solid electrolyte and a covalently grafted polyolefin, wherein the covalently grafted polyolefin includes a polyolefin main chain and a covalently grafted material covalently grafted to the polyolefin main chain.
[0006] In the composite material, the mass ratio between the solid electrolyte and the covalently grafted polyolefin is (0.2 to 1000):1.
[0007] In the composite material, the solid electrolyte is one or more of a sulfide solid electrolyte and an oxide solid electrolyte.
[0008] In the composite material, the oxide solid electrolyte is one or more of LATP, LLTO, LLZO, LLZTO, LLZAO, LLZBO, LLZNO, LLZGO, and LiCPON.
[0009] In the composite material, the sulfide solid electrolyte is one or more of LGPS, LPS, LPSCl, LSnPS, LSiPS, LGSiPS, LA1PS, LGS, LGZS, LSiS, and LSAlS.
[0010] In the composite material, the grafting rate of the covalently grafted polyolefin is 0.2% to 25%.
[0011] In the composite material, the polyolefin backbone includes one or more of a first polyolefin backbone and a second polyolefin backbone;
[0012] Wherein, the first polyolefin main chain has:
[0013] ;
[0014] Wherein, the second polyolefin main chain has:
[0015] ;
[0016] Wherein, m represents the average number of oxyethylene groups, which is an integer between 1 and 20,000, R 1 represents one of hydrogen and C1 to C4 alkyl;
[0017] Wherein, n represents the average number of acrylonitriles, which is an integer between 1 and 1000, R 2 represents one of hydrogen and C1 to C6 alkyl, R 3 represents one of hydrogen and C1 to C6 alkyl.
[0018] In the composite material, the covalent grafting material includes one or more of glycidol and its ester derivatives, 3-(2-thiophene)pyrazole, vinyl imidazole iodide, cyclohexyl methacrylate, dimethylaminoethyl methacrylate, trifluoroethyl methacrylate, tetraethylene glycol dimethacrylate, methyl methacrylate, and methyl cyanoacrylate.
[0019] The second scheme of the present invention is implemented as follows: a method for preparing the above-mentioned composite material, which includes: providing the covalently grafted polyolefin and a slurry, the slurry containing the solid electrolyte; and mixing and stirring the covalently grafted polyolefin and the slurry.
[0020] In the preparation method, the preparation method of the slurry includes: grinding the solid electrolyte; and mixing and stirring the solid electrolyte with a dispersant and a wetting agent.
[0021] In the preparation method, the grinding step includes: mixing the solid electrolyte with a first solvent and stirring to obtain a mixture; and adding grinding balls to the mixture and grinding until the particle size of the solid electrolyte is less than 1000 nm.
[0022] In the preparation method, the first solvent includes one or more of anhydrous ethanol, acetone, and water.
[0023] In the preparation method, the dispersant includes one or more of polyisocyanate, ethyl polyethylene glycol, tert-butyl polyethylene glycol, polyethylene glycol acrylate block copolymer, imidazole compound, and hydroxyl-containing aqueous compound.
[0024] In the preparation method, the wetting agent includes one or more of polyols, silane coupling agents, fatty alcohol polyoxyethylene ethers, acylglycerides and derivatives thereof.
[0025] In the preparation method, the preparation method of the covalently grafted polyolefin includes: mixing the polyolefin main chain with a second solvent and stirring to obtain a mixed solution; and mixing a free radical initiator, the covalently grafted material and the mixed solution and stirring, and then adjusting the pH to perform graft copolymerization.
[0026] In the preparation method, the free radical initiator includes Cl 2 Br 2 , one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, hydroxycyclyl phenyl ketone, cyclohexanone peroxide, tert-butyl hydroperoxide, and isopropylbenzene hydroperoxide.
[0027] In the preparation method, the second solvent includes one or more of ethanol, methanol, acetone, acetonitrile, polyethylene glycol, methacryloyl chloride, sulfuric acid, hydrochloric acid, and deionized water.
[0028] The third embodiment of the present invention is implemented as follows: a current collector includes the above-mentioned composite material.
[0029] According to the present invention, the composite material containing solid electrolyte and covalently grafted polyolefin prepared by mixing high-performance solid electrolyte into covalently grafted polyolefin can improve the electrochemical properties, mechanical properties and ionic conductivity of the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram showing that the composite material of the present invention can form a composite material layer for use in a positive electrode current collector. DETAILED DESCRIPTION
[0031] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0032] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0033] The composite material of the present invention disrupts the order of a single polymer molecular chain to a certain extent by covalently grafting polyolefins, thereby increasing porosity, reducing crystallinity, and increasing the flexibility of the polymer chain, thereby effectively inhibiting the generation of lithium dendrites during the cycle. Moreover, the electrochemical and mechanical properties of the electrolyte are improved and the ionic conductivity is increased by blending the solid electrolyte into the covalently grafted polyolefins.
[0034] The composite material of the present invention can be formed into a composite material layer for use as a current collector. Figure 1 As shown, the current collector is preferably a positive electrode current collector, and in addition to the composite material layer 20 formed by the composite material of the present invention, the positive electrode current collector may further include: a current collector layer 10 and a positive electrode active material layer 30, the current collector layer 10 is arranged on one side of the composite material layer 20, and the positive electrode active material layer 30 is arranged on the other side of the composite material layer 20. The technical core of the present invention lies in the composition of the composite material, and the formation and composition of the current collector layer 10 and the positive electrode active material layer 30 are conventional processes known to those skilled in the art, so it is not necessary to describe them in detail herein.
[0035] The composite material of the present invention comprises at least: a solid electrolyte and a covalently grafted polyolefin. The mass ratio between the solid electrolyte and the covalently grafted polyolefin can be, but is not limited to, (0.2 to 1000):1, and is preferably: 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 2:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, 55:1, 60:1, 65:1 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 100:1, 150:1, 200:1, 250:1, 300:1, 350:1, 400:1, 450:1, 500:1, 550:1, 600:1, 650:1, 700:1, 750:1, 800:1, 850:1, 900:1, 950:1, or 1000:1 or a range between any two of the above ratios. When the mass ratio between the solid electrolyte and the covalently grafted polyolefin is lower than the above numerical range (such as 0.16:1), the increase in the content of the covalently grafted polyolefin will cause the stripping performance to increase sharply and the permeability to decrease; as the SEI film continues to grow, the polarization impedance of the battery continues to increase, and the electrochemical activity of the graphite negative electrode continues to decrease and gradually loses its activity; on the other hand, as the thickness of the SEI film continues to increase, the internal resistance increases rapidly, and a large number of uneven blocky deposits are generated on the surface of the negative electrode. When the mass ratio between the solid electrolyte and the covalently grafted polyolefin is higher than the above numerical range (such as 2000:1), although the conductivity of the solid oxide electrolyte is better than that of the covalently grafted polymer, the ionic conductivity is good, the cycle performance is good, and the raw material cost is low, the interface compatibility of the solid oxide electrolyte itself is poor, and it must be used together with the polymer. When the covalently grafted polymer accounts for 0.05% of the content of the solid oxide electrolyte, the poor interface compatibility of the solid oxide electrolyte is not improved, resulting in the electrolyte dissolving part of the interface during the production of the battery cell, which may cause instantaneous voltage drop or even micro short circuit.
[0036] The term "covalent grafting" used herein can be interchanged with "grafted covalent", which refers to the reaction of adding certain monomers to the presence of a polymer backbone or main chain polymer to carry out a polymerization reaction, and combining the branch polymer components on the backbone polymer through chemical bonds to form branches. It can be seen that the covalently grafted polyolefin includes a polyolefin backbone and a covalently grafted material, and the covalently grafted material is covalently grafted to the polyolefin backbone. The grafting rate of the covalently grafted polyolefin can be expressed by the following formula:
[0037] = ;
[0038] is the grafting rate of the polymer, W1 is the mass of the polymer before grafting, and W2 is the mass of the polymer after grafting. The grafting rate of the covalently grafted polyolefin can be, but is not limited to, 0.2% to 25%, and is preferably: 0.2%, 0.4%, 0.6%, 0.8%, 1%, 2.5%, 5%, 7.5%, 10%, 12.5%, 15%, 17.5%, 20%, 22.5%, or 25% or the range between any two of the above ratios. The polyolefin backbone may include, but is not limited to, one or more of the first polyolefin backbone and the second polyolefin backbone.
[0039] Suitable first polyolefin backbones have:
[0040] m represents the average number of oxyethylene groups (the average number of oxyethylene groups in the presence of one first polyolefin main chain), which can be, but is not limited to, an integer between 1 and 20,000, preferably 100, 200, 300, 400, 500, 600, 800, 900, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 70 ... 18000, 18500, 19000, 19500, or 20000, or a range between any two of the above ratios. 1 represents one of hydrogen and C1 to C4 alkyl, and is preferably hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, or t-butyl.
[0041] Suitable second polyolefin backbones have:
[0042] n represents the average number of acrylonitriles (the average number of acrylonitriles present in the presence of one second polyolefin main chain), which can be, but is not limited to, an integer between 1 and 1000, preferably 50, 100, 200, 300, 400, 500, 600, 700, 800, 900, or 1000 or a range between any two of the above ratios. 2 represents one of hydrogen and C1 to C6 alkyl, and is preferably hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, t-butyl, n-pentyl, isopentyl, neopentyl, sec-pentyl, t-pentyl, n-hexyl, isohexyl, sec-hexyl, or t-hexyl; R3 represents one of hydrogen and C1 to C6 alkyl, and is preferably hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, t-butyl, n-pentyl, isopentyl, neopentyl, sec-pentyl, t-pentyl, n-hexyl, isohexyl, sec-hexyl, or t-hexyl.
[0043] In addition, under the condition that the first polyolefin backbone and the second polyolefin backbone exist at the same time, the mass ratio between the first polyolefin backbone and the second polyolefin backbone can be, but is not limited to, 1:(0.2 to 700), and is preferably: 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:15, 1:16, 1:17, 1:18, 1:19, 1:10, 1:15, 1:19, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:10 ...8, 1:19, 1:11 :20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:55, 1:60, 1:65, 1:70, 1:75, 1:80, 1:85, 1:90, 1:95, 1:100, 1:150, 1:200, 1:250, 1:300, 1:350, 1:400, 1:450, 1:500, 1:550, 1:600, 1:650, or 1:700 or a range between any two of the above ratios. When the mass ratio between the first polyolefin main chain and the second polyolefin main chain is lower than the above numerical range (such as 1:1000), after sufficient dispersion and mixing, the block shadow part cannot be completely decomposed, and after filtering to make a slurry product for coating, the peeling force is reduced, and the test finds that the internal resistance is increased, and the ionic conductivity and decomposition voltage are reduced. When the mass ratio between the first polyolefin main chain and the second polyolefin main chain is higher than the above numerical range (such as 1:0.1), the grafting rate after dissolution is very low, and the slurry is made into a battery cell. Testing shows that the decomposition voltage is low.
[0044] Suitable covalent grafting materials may include, but are not limited to, one or more of glycidol and its ester derivatives, 3-(2-thiophene)pyrazole, vinyl imidazole iodide, cyclohexyl methacrylate, dimethylaminoethyl methacrylate, trifluoroethyl methacrylate, tetraethylene glycol dimethacrylate, methyl methacrylate, and methyl cyanoacrylate.
[0045] Suitable solid electrolytes may include, but are not limited to, one or more of sulfide solid electrolytes and oxide solid electrolytes. Sulfide solid electrolytes may include, but are not limited to, one or more of LGPS, LPS, LPSCl, LSnPS, LSiPS, LGSiPS, LAlPS, LGS, LGZS, LSiS, LSAlS. Oxide solid electrolytes may include, but are not limited to, one or more of LATP, LLTO, LLZO, LLZTO, LLZAO, LLZBO, LLZNO, LLZGO, LiCPON; generally, LATP can be represented by the chemical formula Li 1+x Al x M 2-x (PO 4 ) 3 (0 ≤ x ≤ 0.7, M is Ti or Ge), LLTO can be represented by the chemical formula Li 3x La 2 / 3-x TiO 3 (0 < x < 0.16), LLZTO can be represented by the chemical formula Li 7-x La 3 Zr 2-x Ta x O 12 (0 ≤ x ≤ 2), LiCPON can be represented by the chemical formula Li x C y PO 4-z N z (x > 3, 0 < y < 1, 0 < z < 1).
[0046] The following exemplarily illustrates the preparation method of the composite material of the present invention. It should be noted that the described preparation method should not impose any limitation on the composite material of the present invention, that is to say, the composite material of the present invention can also be obtained through other preparation methods.
[0047] First, perform the providing step: provide covalently grafted polyolefin and a slurry containing a solid electrolyte.
[0048] The preparation method of the slurry may include, but is not limited to: grinding the solid electrolyte; and mixing and stirring the solid electrolyte with a dispersant and a wetting agent. The dispersant may include, but is not limited to, one or more of polyisocyanate, ethyl polyethylene glycol, tert-butyl polyethylene glycol, polyethylene glycol acrylate block copolymer, imidazole compound, and hydroxyl-containing aqueous compound, and the wetting agent may include, but is not limited to, one or more of polyols, silane coupling agents, fatty alcohol polyoxyethylene ethers, acylglycerides, and derivatives thereof. In addition, the grinding step may include, but is not limited to: mixing the solid electrolyte with the first solvent and stirring to obtain a mixture; and adding grinding balls to the mixture and grinding until the particle size of the solid electrolyte is less than 1000 nm. The first solvent may include, but is not limited to, one or more of anhydrous ethanol, acetone, and water. The preparation method of the slurry can be exemplified by: adding the solid electrolyte to the first solvent (such as a mixture of anhydrous ethanol and water) multiple times, stirring at a speed of 1000 rpm to 5000 rpm, mixing the solid electrolyte with grinding balls (such as zirconia balls) at a weight ratio of 1:1 to 10, grinding at a speed of 1000 rpm to 3000 rpm for 1 hour to 12 hours until the particle size of the solid electrolyte is 100 nm to 1000 nm, passing through a 100 mesh to 1500 mesh sieve, adding a dispersant (such as polyisocyanate) and stirring, reducing the speed to 200 rpm to 1000 rpm, adding a wetting agent (such as a mixture of a silane coupling agent and a polyol), and continuing to stir until a uniform slurry is obtained.
[0049] The preparation method of the covalently grafted polyolefin may include but is not limited to: mixing the polyolefin backbone with the second solvent and stirring to obtain a mixed solution; and mixing a free radical initiator, a covalently grafted material and the mixed solution and stirring, and then adjusting the pH to perform graft copolymerization. The free radical initiator may include but is not limited to Cl 2 Br 2, azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, hydroxycyclyl phenyl ketone, cyclohexanone peroxide, tert-butyl hydroperoxide, isopropylbenzene hydroperoxide, and the second solvent may include but is not limited to one or more of ethanol, methanol, acetone, acetonitrile, polyethylene glycol, methacryloyl chloride, sulfuric acid, hydrochloric acid, and deionized water. The preparation method of the covalently grafted polyolefin may include, for example, mixing a polyolefin backbone with a second solvent, heating the mixture to 55°C to 80°C at a heating rate of 0.5°C / min to 5°C / min, and stirring until the mixed solution becomes clear and light yellow; adding the covalently grafted material to the mixed solution in an appropriate proportion, adding a free radical initiator, and continuously stirring the reaction for 1 hour to 12 hours, and adjusting the pH to an appropriate condition (e.g., pH 6.0 or less, preferably 6.0, 5.9, 5.8, 5.7, 5.6, 5.5, 5.4, 5.3, 5.2, 5.1, 5.0, 4.9, 4.8, 4.7, 4.8) with the second solvent; .6, 4.5, 4.4, 4.3, 4.2, 4.1, 4.0, 3.9, 3.8, 3.7, 3.6, 3.5, 3.4, 3.3, 3.2, 3.1, 3.0, 2.9, 2.8, 2.7, 2.6, 2.5, 2.4, 2.3, 2.2, 2.1, 2.0, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, or 1.0 or a range between any two of the above ratios) for graft copolymerization to form a covalently grafted polyolefin; and washing the covalently grafted polyolefin, heating to 55° C. to 80° C., and filtering multiple times to obtain the covalently grafted polyolefin.
[0050] Next, a mixing step is performed: the covalently grafted polyolefin is mixed with the slurry and stirred. In addition, the pH value can be adjusted during the mixing and stirring to ensure that the particle size and viscosity of the obtained composite material meet the requirements.
[0051] The present invention is further illustrated by the following examples:
[0052] Example 1
[0053] 42 kg of solid electrolyte Li 1+x Al x Ge 2-x (PO 4 ) 3(0≤x≤0.7) is added to a mixed solvent of 56 kg of anhydrous ethanol and deionized water (molar ratio of 1:3.5) in three times in a weight ratio of 6:2:2, and is uniformly stirred at a high speed of 2000 rpm, and then mixed in a weight ratio of solid electrolyte: zirconium oxide = 1:5, and ground using a high-speed grinder at 1500 rpm for 4 to 6 hours, and the temperature of the grinder is controlled below 60°C to a particle size below 500 nm, and passed through a 100-mesh sieve, 1.2 kg of dispersant polyisocyanate is added and stirred rapidly, and after reducing the speed to 500 rpm, a wetting agent mixture of silane coupling agent (3-glycidyl propoxy) trimethoxysilane and polyol 1,3-butanediol with a molar ratio of 15:1 (the total weight of the two is 0.8 kg) is slowly added, and stirring is continued to form a uniform slurry.
[0054] The covalent grafting process of the covalently grafted polyolefin material comprises the following steps:
[0055] Step S1: Add polyethylene oxide (average number of ethylene oxide groups: 1500) and polyacrylonitrile (average number of acrylonitrile monomer: 300) materials (total weight of the two is 2.4 kg) in a mass ratio of 1:3 into a four-necked pressure reaction vessel, add 16.7 kg of a mixed solvent of acetone and deionized water (molar ratio: 1:3), slowly heat to 65°C at a rate of 0.5°C / min and continue stirring until the solution becomes a light yellow clear liquid;
[0056] Step S2: Add the covalent grafting materials vinyl imidazole iodide and tetraethylene glycol dimethacrylate in a molar ratio of 1:2 (the total weight of the two is 0.8 kg) to the reaction container, slowly add the free radical initiators azobisisoheptanenitrile and cyclohexanone peroxide in a molar ratio of 8:1 (the total weight of the two is 0.02 kg), continue stirring for more than 5 hours, and adjust the pH to 5.6 with dilute sulfuric acid to form a uniform and stable covalent graft copolymer initial material;
[0057] Step S3: After the filtrate is rinsed with a large amount of acetone solution, the temperature is raised to 65° C., and after multiple filtrations, a uniform covalently grafted polyolefin material is obtained.
[0058] The uniform liquid of the covalently grafted polyolefin material is slowly added dropwise to the uniform solution of the solid electrolyte, wherein the mass ratio between the solid electrolyte and the covalently grafted polyolefin material is 2:1, and stirred at a uniform speed, while the particle size and viscosity of the product are tested at continuous intervals, and the pH is adjusted to ensure that the required results are achieved.
[0059] Example 2
[0060] 34.5 kg of solid electrolyte The mixture was added into a mixed solvent of 63.8 kg of anhydrous ethanol and deionized water (molar ratio of 1:3.5) in three times in a weight ratio of 7:2:1, and stirred evenly at a high speed of 1200 rpm. Then, the mixture was mixed in a weight ratio of solid electrolyte to zirconium oxide of 1:2, and ground at 1130 rpm using a high-speed grinder for 2 to 4 hours until the particle size was below 300 nm. The mixture was passed through a 1250 mesh sieve, and tert-butyl polyethylene glycol and a hydroxyl-containing aqueous compound in a molar ratio of 5:1 as a dispersant (the total weight of the two was 1.6 kg) were added and stirred rapidly. After reducing the speed to 500 rpm, 0.1 kg of a wetting agent fatty alcohol polyoxyethylene ether was slowly added, and stirring was continued until a uniform slurry was obtained.
[0061] The covalent grafting process of the covalently grafted polyolefin material comprises the following steps:
[0062] Step S1: Add polyethylene oxide (average number of ethylene oxide groups: 1500) and polyacrylonitrile (average number of acrylonitrile monomer: 300) materials (total weight of 1.1 kg) in a mass ratio of 2:1 into a four-necked pressure reaction vessel, add 8.6 kg of a mixed solvent of acetone and deionized water (molar ratio: 1:3), slowly heat to 65°C at a rate of 0.5°C / min and continue stirring until the solution becomes a light yellow clear liquid;
[0063] Step S2: add the covalent grafting materials glycidol and its ester derivatives and cyclohexyl methacrylate in a molar ratio of 1:5 (the total weight of the two is 0.2 kg) to the reaction container, slowly add the free radical initiators azobisisoheptanenitrile and tert-butyl hydroperoxide in a molar ratio of 3:1 (the total weight of the two is 0.05 kg), continue stirring for more than 12 hours, and adjust the pH to 6.0 with dilute hydrochloric acid to form a uniform and stable covalent graft copolymer initial material;
[0064] Step S3: After the filtrate is rinsed with a large amount of acetonitrile solution, the temperature is raised to 80° C., and after multiple filtrations, a uniform covalently grafted polyolefin material is obtained.
[0065] The uniform liquid of the covalently grafted polyolefin material is slowly added dropwise to the uniform solution of the solid electrolyte, wherein the mass ratio between the solid electrolyte and the covalently grafted polyolefin material is 30:1, and stirred at a uniform speed, while the particle size and viscosity of the product are tested at continuous intervals, and the pH is adjusted to ensure that the required results are achieved.
[0066] The composite materials of Examples 1 and 2 are prepared into positive electrode current collectors by adopting the following process, and are combined with other components to form lithium-ion batteries: pole piece cutting → slurry coating → baking → lamination → pole ear welding → shelling → drying → liquid injection → sealing → hot and cold pressing → formation → capacity division → voltage and internal resistance measurement → standard cycle → safety performance.
[0067] The battery cycle, safety and electrical performance test standards refer to: GB / T31484-2015 Cycle life requirements and test methods for power batteries for electric vehicles, GB / T38031-2020 Safety requirements and test methods for power batteries for electric vehicles, and GB / T31486-2015 Electrical performance requirements and test methods for power batteries for electric vehicles.
[0068] The test formula for ionic conductivity is:
[0069] Where:
[0070] σ is the ionic conductivity of the solid electrolyte ceramic sheet, in Siemens per centimeter (S / cm);
[0071] L is the thickness of the solid electrolyte ceramic sheet, in centimeters (cm);
[0072] S is the cross-sectional area of the solid electrolyte ceramic sheet, in square centimeters (cm 2 );
[0073] R is the resistance measurement value of the solid electrolyte ceramic sheet in ohms (Ω).
[0074]
[0075] Table 1 shows the decomposition voltage and ionic conductivity of the battery prepared using the composite materials of Examples 1 and 2. It was particularly found that different heating rates of the polyolefin main chain in Example 1 (i.e., when the heating rate is changed by only one factor) will affect the stability of the covalent graft copolymer and the first efficiency (%) and K value (mV / d) of the battery; specifically, when the heating rate is 0.5°C / min, a uniform and stable covalent graft copolymer can be obtained, which can increase the first efficiency of the battery by 3% and reduce the K value of the battery by 5% compared with the battery containing only solid electrolyte as the positive current collector; when the heating rate is 2°C / min, a uniform and stable covalent graft copolymer can be obtained, which can increase the first efficiency of the battery by 1% and reduce the K value of the battery by 3% compared with the battery containing only solid electrolyte as the positive current collector; when the heating rate is 5°C / min, a covalent graft copolymer that can be stored for a long time cannot be obtained, which can increase the first efficiency of the battery by 0.5% and reduce the K value of the battery by 1% compared with the battery containing only solid electrolyte as the positive current collector.
[0076]
[0077] Table 2 shows the capacity retention performance of the battery prepared using the composite materials of Examples 1 and 2. It was particularly found that different covalent grafting pH conditions in Examples 1 and 2 (i.e., when only the pH value is changed by a single factor) will affect the capacity retention performance of the battery. Specifically, when the covalent grafting pH is 5.6 in Example 1, the long cycle capacity retention rate of the battery is ≥98% for 1000 cycles, and the rate capacity retention rate is 85%; when the pH is ≥6.5, the long cycle capacity retention rate drops to 94% to 97% for 1000 cycles, and the rate capacity retention rate also drops to 80%. More specifically, when the covalent grafting pH is 6.0 in Example 2, the long cycle capacity retention rate of the battery is ≥98.5% for 1000 cycles, and the rate capacity retention rate is 85%; when the pH is ≥6.8, the long cycle capacity retention rate drops to 95% to 98% for 1000 cycles, and the rate capacity retention rate also drops to 80%.
[0078] Finally, solid electrolytes include sulfide solid electrolytes and oxide solid electrolytes. Sulfide solid electrolytes mainly have good ionic conductivity and electrochemical stability, and usually need to be combined with positive and negative electrode materials and other battery components. Sulfide solid electrolytes themselves do not have sufficient adhesion. Oxide solid electrolytes are usually granular powder substances, which usually do not have adhesiveness themselves. Overall, solid electrolytes cannot be used alone. In addition, covalently grafted polyolefins are only an effective method for covalently connecting functional molecules or polymers to polyolefin main chains through chemical reactions, and modifying the main chain surface, which can give polyolefins new properties. The polyolefins directly applied to the battery core have poor ionic conductivity, electrochemical stability, internal resistance and cycle performance, and cannot be directly applied alone. Therefore, the present invention improves the electrochemical properties, mechanical properties and ionic conductivity of the electrolyte by blending high-performance solid electrolytes into covalently grafted polyolefins. Based on the fact that high-performance solid electrolytes alone and covalently grafted polyolefins alone cannot be applied to current collectors, it is obvious that the present invention does bring significant progress.
[0079] The above contents involving common knowledge are not described in detail, and those skilled in the art can understand them.
[0080] The above descriptions are only some specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the protection scope of the present invention. The technical scope of the present invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A composite material, characterized in that: include: A solid electrolyte and a covalently grafted polyolefin, wherein the covalently grafted polyolefin comprises a polyolefin main chain and a covalently grafted material covalently grafted to the polyolefin main chain; The solid electrolyte is one or more of a sulfide solid electrolyte and an oxide solid electrolyte; The covalent grafting material includes one or more of glycidol and its ester derivatives, 3-(2-thiophene)pyrazole, vinyl imidazole iodide, cyclohexyl methacrylate, dimethylaminoethyl methacrylate, trifluoroethyl methacrylate, tetraethylene glycol dimethacrylate, methyl methacrylate, and methyl cyanoacrylate; The solid electrolyte is blended into the covalently grafted polyolefin; The mass ratio between the solid electrolyte and the covalently grafted polyolefin is (2 to 1000): 1; The polyolefin backbone comprises a first polyolefin backbone and a second polyolefin backbone; Wherein, the first polyolefin main chain has: ; Wherein, the second polyolefin main chain has: ; Wherein, m represents the average number of oxyethylene groups, which is an integer between 1 and 20,000, and R1 represents one of hydrogen and C1 to C4 alkyl; Wherein, n represents the average number of acrylonitrile, which is an integer between 1 and 1000, R2 represents one of hydrogen and C1 to C6 alkyl, and R3 represents one of hydrogen and C1 to C6 alkyl.
2. The composite material according to claim 1, characterized in that The oxide solid electrolyte is one or more of LATP, LLTO, LLZO, LLZTO, LLZAO, LLZBO, LLZNO, LLZGO, and LiCPON, and the sulfide solid electrolyte is one or more of LGPS, LPS, LPSCl, LSnPS, LSiPS, LGSiPS, LAIPS, LGS, LGZS, LSiS, and LSAlS.
3. The composite material according to claim 1, characterized in that The grafting rate of the covalently grafted polyolefin is 0.2% to 25%.
4. A method for preparing the composite material according to any one of claims 1 to 3, characterized in that: include: Providing the covalently grafted polyolefin and a slurry, wherein the slurry contains the solid electrolyte; as well as The covalently grafted polyolefin is mixed with the slurry and stirred.
5. The preparation method according to claim 4, characterized in that: The preparation method of the slurry comprises: grinding the solid electrolyte; and The solid electrolyte is mixed with a dispersant and a wetting agent and stirred.
6. The preparation method according to claim 5, characterized in that: The grinding step comprises: mixing the solid electrolyte with a first solvent and stirring to obtain a mixture; and Add grinding balls to the mixture and grind until the particle size of the solid electrolyte is below 1000 nm.
7. The preparation method according to claim 6, characterized in that: The first solvent includes one or more of anhydrous ethanol, acetone, and water.
8. The preparation method according to claim 5, characterized in that: The dispersant includes one or more of polyisocyanate, ethyl polyethylene glycol, tert-butyl polyethylene glycol, polyethylene glycol acrylate block copolymer, imidazole compound, and hydroxyl-containing aqueous compound.
9. The preparation method according to claim 5, characterized in that: The wetting agent includes one or more of polyols, silane coupling agents, fatty alcohol polyoxyethylene ethers, acylglycerides and derivatives thereof.
10. The preparation method according to claim 4, characterized in that: The preparation method of the covalently grafted polyolefin comprises: mixing the polyolefin backbone with a second solvent and stirring to obtain a mixed solution; and The free radical initiator, the covalent grafting material and the mixed solution are mixed and stirred, and then the pH is adjusted to carry out graft copolymerization.
11. The preparation method according to claim 10, characterized in that: The free radical initiator includes one or more of Cl2, Br2, azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, hydroxycyclyl phenyl ketone, cyclohexanone peroxide, tert-butyl hydroperoxide, and isopropylbenzene hydroperoxide.
12. The preparation method according to claim 10, characterized in that: The second solvent includes one or more of ethanol, methanol, acetone, acetonitrile, polyethylene glycol, methacryloyl chloride, sulfuric acid, hydrochloric acid, and deionized water.
13. A current collector, characterized in that: Comprising the composite material according to any one of claims 1 to 3.
Citation Information
Patent Citations
Solid electrolyte composition, solid electrolyte-containing sheet, all-solid-state secondary battery, and method for producing solid electrolyte-containing sheet and all-solid-state secondary battery
CN109155162A
Preparation method and application of dual-modified solid electrolyte membrane
CN114335710A
Binder and preparation method thereof, pole piece and battery
CN118638497A